Crowdsourcing metadata for audiovisual cultural heritage : Finnish full-length films, 1946–1985 - Hannu Salmi; Kimmo Laine; Tommi Römpötti; Noora Kallioniemi; Elina Karvo (Latvia, 2026)
This paper is based on a crowdsourcing project which was realised at the School of History, Culture and Arts Studies of the University of Turku between the years 2013–2018. The idea was to develop a format through which long-term crowdsourcing could be integrated into the humanities curriculum. The project was realised in close cooperation with the National Audiovisual Institute (KAVI) in Finland. The aim was to help KAVI in developing its open database for Finnish cinema, Elonet, by engaging both graduate and postgraduate students in producing keywords, genre characterisations, plot summaries and other relevant fields of information for Finnish cinema. In total, the project produced metadata for 572 full-length films, both fiction films and long documentaries that had their theatre release between the years 1946 and 1985. The amount is substantial considering that, to date, around 1,600 full-length films have been released in Finland. At the same time, it produced a successful model for drawing on crowdsourcing in the classroom.
DHN 2020 Digital Humanities in the Nordic Countries 5th Conference